PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA PEKANBARU - Jordi Satria Nanda; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Basically the activities of Micro, Small and Medium Enterprises (SMEs) lack of legal protection from the government, it is because the government should provide a means of marketing, but it turns out it is not done because the government only provides training to businesses, and does not carry out supervision of their coaching and the development of micro, small, and medium to obtain financing and services / financial product and no one gives a means of marketing.The purpose of this thesis are: First, to determine the Legal Protection Against Perpetrators of Micro, Small and Medium Enterprises (SMEs) in the city of Pekanbaru. Second, to determine factors inhibiting the Legal Protection Against Perpetrators of Micro, Small and Medium Enterprises (SMEs) in the city of Pekanbaru.This research is a sociological juridical legal research or direct writers to conduct research in the area of Pekanbaru city, namely the small and medium entrepreneurs in the city of Pekanbaru as rattan enterprises located in the territory Rumbai in order to provide complete and clear picture of the issues examined.The final conclusion, First, the Legal Protection Against Perpetrators of Micro, Small and Medium Enterprises (SMEs) in the city of Pekanbaru is not going well because the government only in the form of the creation of a business environment conducive to business development and human resources capacity building through Technical Assistance in the form of training and were not accompanied by capital requirements and Enhancing productivity and mastery of technology through the help of production facilities and infrastructure such as rattan, licensing form of CV, Certification Trademarks SMEs, and development in the field of design and technology and the government has not been able to provide a means of marketing well to businesses mainly to businesses rattan craftsmen. Second, Inhibiting Factors Legal Protection Against Perpetrators of Micro, Small and Medium Enterprises (SMEs) in the city of Pekanbaru is seen from entrepreneurs is that many business operators rattan no training, do not master the field of design and technology, does not meet the requirements in licensing in order to obtain the certificate brands trade. While the government is that the government does not have sufficient funds to carry out the development of Micro, Small and Medium Enterprises (SMEs), and it's hard to do marketing the production because of competition from outside the region and from abroad. The suggestion of the results of this study are. First, Should the government more active in the provision of capital requirements as well as marketing. Secondly, We recommend that the government opened an innovation to open a global marketing.Keywords: Legal Protection-business communities, Micro, Small and Medium Enterprises (SMEs).